STUDI KUALITATIF; PENGALAMAN REMAJA DALAM MENGHADAPI PERUBAHAN SOSIAL BUDAYA DAN TANTANGAN KESEHATAN REPRODUKSI DI ERA DIGITAL - Aswar, Aswar; Adam, Arlin; Alim, Andi; Munadhir, Munadhir; Adnan, Yudhi (Jurnal Kesehatan Marendeng, 2025)
Socio-cultural changes driven by the development of digital technology have significantly impacted adolescents' lives, particularly in terms of social interaction, cultural values, and understanding of reproductive health. This study aims to explore in depth the subjective experiences of adolescents in facing socio-cultural changes and reproductive health challenges in the digital era. A qualitative approach with a phenomenological study design was employed, involving adolescent informants aged 15–19 years in Banggae Timur Subdistrict, Majene Regency, West Sulawesi. Data were collected through in-depth interviews, observation, and document analysis, and were examined using thematic analysis techniques. The findings reveal a shift in communication patterns from face-to-face interaction to social media-based communication, which affects social closeness and interpersonal skills. Adolescents also face challenges in understanding reproductive health due to limited education from schools and families, leading them to rely heavily on digital media sources that may not be reliable. Nevertheless, some adolescents demonstrated critical attitudes in filtering digital cultural influences and relied on parents as trusted sources of information. Social support from the environment, particularly families, plays a vital role in shaping adolescents’ perceptions and behaviors. Adolescents expressed the need for improved reproductive health education in schools and the provision of safe, accessible, and stigma-free counseling services. This study recommends the integration of reproductive health education into the school curriculum, teacher training, enhancement of adolescents’ digital literacy, and the development of policies based on contextual needs.